2010
DOI: 10.1021/bi902021d
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium tuberculosis UvrD1 and UvrA Proteins Suppress DNA Strand Exchange Promoted by Cognate and Noncognate RecA Proteins

Abstract: DNA helicases are present in all kingdoms of life and play crucial roles in processes of DNA metabolism such as replication, repair, recombination, and transcription. To date, however, the role of DNA helicases during homologous recombination in mycobacteria remains unknown. In this study, we show that Mycobacterium tuberculosis UvrD1 more efficiently inhibited the strand exchange promoted by its cognate RecA, compared to noncognate Mycobacterium smegmatis or Escherichia coli RecA proteins. The M. tuberculosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 75 publications
0
30
0
Order By: Relevance
“…UvrD homologues can also act as translocases, and in this way they are able to displace proteins bound to DNA (1). It is possible that translocase activity of M. tuberculosis UvrD1 could contribute to clearing RecA from the DNA at fork structures (9,46). This behavior would be similar to that of the E. coli RecG helicase, which has been shown to be involved in the recovery of stalled replication forks (41).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…UvrD homologues can also act as translocases, and in this way they are able to displace proteins bound to DNA (1). It is possible that translocase activity of M. tuberculosis UvrD1 could contribute to clearing RecA from the DNA at fork structures (9,46). This behavior would be similar to that of the E. coli RecG helicase, which has been shown to be involved in the recovery of stalled replication forks (41).…”
Section: Discussionmentioning
confidence: 96%
“…It is thought that this action is at least partly mediated by the ability of these enzymes to restrict the actions of RecA at blocked replication forks (1,31). Indeed, biochemical studies have shown that M. tuberculosis UvrD1 suppresses DNA strand exchange reactions catalyzed by RecA in vitro (46). UvrD homologues can also act as translocases, and in this way they are able to displace proteins bound to DNA (1).…”
Section: Discussionmentioning
confidence: 99%
“…The apparent requirement for ATP hydrolysis and/or DNA translocation, but not helicase, activity suggests that the essential function of UvrD2 is most likely to involve some such DNA translocation and, potentially, protein displacement. Mycobacterial UvrD1 can function to inhibit RecA-mediated strand exchange (28); whether UvrD2 also plays a role in regulating recombination remains to be seen. The identification of the crucial role of UvrD2 in M. tuberculosis growth and survival will require additional studies.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it would appear that it is UvrD1 that functions in NER in M. tuberculosis. Interestingly, M. tuberculosis UvrD1 also suppresses DNA strand-exchange reactions catalyzed by RecA (28), and M. smegmatis UvrD1 appears to play a role in regulating recombination (10), suggesting that mycobacterial UvrD1 has further roles outside NER.…”
mentioning
confidence: 99%
“…Co-immunoprecipitation-Assays were performed as described earlier (46). Whole-cell lysates (in 20 mM Tris-HCl, pH 7.5, 100 mM NaCl, and 0.5 mM EDTA) from E. coli cells expressing MtRecD and MtRecA were treated with 50 g/ml DNase I at 37°C for 1 h. The interaction between proteins in the wholecell lysates was facilitated by incubation with gentle stirring for 6 h at 4°C.…”
Section: Methodsmentioning
confidence: 99%